Economic Issues of Current Development of British Food Production - Kubátová, Andrea; Pošvicová, Zdena, 1951-; Němcová, Ingeborg, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The thesis describes the current situation and trends influencing food production in the UK. It focuses on the position of agriculture, notably food production, in the national economy as well as in the context of international trade. The thesis also contains a case study describing the presence of British foods on the Czech Market. The aim of the thesis is to evaluate and analyse the current position of small producers and farms on the UK food market and their future potential, primarily with regard to organic and local production. All the main features are summarized in the SWOT analysis.
Vedoucí práce: Zdena Pošvicová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses